Kesadaran Hukum Warga Masyakat terhadap Penegakan Hukum di Wilayah Perbatasan Negara Republik Indonesia dengan Negara Demokratik Timor Leste - Simon Nahak; I Ketut Widia; Alarico Perman (Postgraduated Community Service Journal, 2020)
The aim of this community service is to find out the factors that cause the community's legal awareness of Law Enforcement in the border territory of the Republic of Indonesia with the Democratic State of Timor Leste and describe the Law Enforcement Practices that apply in each State as the basis for the strength of the law binding the community's legal awareness in the border territory of the Republic of Indonesia with the Democratic State of Timor Leste. This research method is Normative Juridical and Empirical Juridical (mix method). The types of data that support this research are primary data and secondary data. Factors that cause public legal awareness of law enforcement in the border territory of the Republic of Indonesia and the Democratic State of Timor Leste, are factors from within oneself, namely from their mind to obey the law and external factors due to the influence of family, environment, especially law enforcement practices. Law enforcement practices in the Republic of Indonesia through 2 (two) methods namely; Through Non-Litigation and Litigation methods.